A Text Mining Implementation Based on Twitter Data to Analyse Information Regarding Corona Virus in Indonesia - Enda Esyudha Pratama; Rizqia Lestika Atmi (Universitas Pendidikan Indonesia, 2020)
CORONA virus outbreak (COVID-19) began to infect almost all countries in early 2020 including Indonesia. Since its distribution, various information has been spread in the community from various sources, one of them is social media. Various terms also appear on social media related to the corona virus. This study analyzes related terms that emerge from social media-based. The data used was sourced from Twitter in the past month where the data processed was text data. The method used is text mining. Text Mining is a method used to extract important information from a group of texts. From the results of the research conducted, there are several terms or information that tend to appear frequently on social media, namely “PSBB”, “new normal”, “karantina”, and “juru bicara Dr. Reisa”.